Cytotoxicity of leachate from the final disposal of water treatment plant sludge - Mirella Bianca Gama de Almeida; Amanda Maria Dantas de Jesus; Adriane Xavier de Morais; Renata Falchete do Prado; Fabiana Alves Fiore (Cleaner Water)
The final disposal of Water Treatment Plant Sludge (WTPS) in soils can generate leachates with cytotoxic potential due to residual metals and organic compounds. This study evaluated the cytotoxicity of leachates derived from simulated sanitary landfills, dedicated landfills, and geotechnical applications using WTPS. The simulations employed centrifuged, thermally dried, and naturally dried sludge in thirteen reactors replicating disposal conditions at a pilot scale. The reactors were operated for 12 months under simulation of real precipitation, with monthly leachate collections. Samples were analyzed for cell viability using the MTT assay on human keratinocytes and for metal concentrations (Al, Ba, Co, Fe, Mn, and Zn) using ICP-OES. The highest concentrations of heavy metals (mg/L) in the leachate were: manganese (292.0), iron (51.32), aluminium (5.03), and barium (4.1). Median values show higher barium in the dry season and manganese influenced by a peak, though more widespread in the rainy season. Among the treatments evaluated, reactors containing thermally dried sludge presented the most pronounced cytotoxic effects. It was also found that the dedicated landfill showed the worst cytotoxicity conditions, with cell viability of less than 50 per cent. The study demonstrates that sludge drying methods, disposal type, and climatic seasonality directly influence leachate toxicity, emphasizing the importance of cytotoxic analysis as a complementary tool in environmental waste management. HaCaT cells are a well-established and reproducible model for studying the effects of solid waste on the human skin response. They offer practical advantages in terms of availability, robustness, and consistency in cytotoxicity tests.